4m+4=10m-62

Simple and best practice solution for 4m+4=10m-62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4m+4=10m-62 equation:


Simplifying
4m + 4 = 10m + -62

Reorder the terms:
4 + 4m = 10m + -62

Reorder the terms:
4 + 4m = -62 + 10m

Solving
4 + 4m = -62 + 10m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-10m' to each side of the equation.
4 + 4m + -10m = -62 + 10m + -10m

Combine like terms: 4m + -10m = -6m
4 + -6m = -62 + 10m + -10m

Combine like terms: 10m + -10m = 0
4 + -6m = -62 + 0
4 + -6m = -62

Add '-4' to each side of the equation.
4 + -4 + -6m = -62 + -4

Combine like terms: 4 + -4 = 0
0 + -6m = -62 + -4
-6m = -62 + -4

Combine like terms: -62 + -4 = -66
-6m = -66

Divide each side by '-6'.
m = 11

Simplifying
m = 11

See similar equations:

| -7/10m=-1324/24 | | 4+17n-3=9n+85-47 | | 100/900=85/x | | Y=-2x^3-2x^2+60x | | ax-2cx+4ay-8cy= | | 18-8-2=.5(18-2) | | -27+3*27=27+27 | | -u+106=240 | | c-3=2-3 | | 2-4-3-4=4 | | 267=158-u | | 2d+2=3d-4 | | Y=-1/4-4-5 | | 10-6*-3=2(-3-3) | | 27+9w=12w | | 2d+3=3d-4 | | 10-6x-3=2(-3-3) | | 5.2+1.2n=1.84 | | 10u=54+u | | 2(-2)-3+(-2)+1= | | 2x-20=3x+6 | | 0.5x+x=169 | | -3/7(-40-2) | | Cos(x)=0.018 | | 18=-3/7(x-2) | | 3(2x-5y)=z | | -5(8r+3)=-5(7r-5) | | 1(8+x)=7 | | 6c+11=2c+51 | | .5(x+8)=-5 | | 6-22(x+6)=2 | | 4x-7(-7-9)=42 |

Equations solver categories